TEACHING PART OF SPEECH AND WORD GROUPS AS UNITS OF MEANING IN ESP SPEAKING CLASS - Urwatus Silvia Rahmah (Journal of English for Academic and Specific Purposes)
English for Specific Purposes (ESP) is known as a learner-centered approach to teach English as a foreign or second language. Students learn English for a specific purpose, represented by studying subject matter, to gain and develop appropriate knowledge and skills through English. They have to perform task in English, meanwhile they are also supposed to be mastered in speaking skill. The objective of this paper is to build the student’s speaking ability effectively by using English. Teaching part of speech and word groups as units of meaning are used in the class. They have to know the words first and then able to classify them as basic of their speaking. The activities include in some parts, they have listening section to start the activity, then grouping the students and asking them to tell the information in front of the class. The aims of this activity are to encourage their competence in English speaking and also make them involve in speaking class. Thus, this paper aims to give a clear explanation and a deeper insight about teaching part of speech and word groups as unit of meaning, stimulate all of teachers of ESP to implement the material in their teaching processes and make them realize in choosing the appropriate material to teach their students.